Urgensi Perjanjian Perkawinan dalam Membentuk Keluarga Sakinah Perspektif Hukum Keluarga Islam - Al-Ghifarry, Idrus; Ja'far, A. Kumedi; Faizal, Liky (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2021)
This research was made to analyze the urgency of the marriage agreement in marriage. To analyze the urgency of the marriage agreement in forming a sakinah family in the perspective of Islamic Family Law. This type of research is library research. This research is descriptive in nature, namely by using qualitative methods. The results of this study show that the urgency of the marriage agreement is that the marriage agreement has good benefits as a preventive measure in the event of a divorce because the marriage agreement will facilitate the distribution of assets. The urgency of the marriage agreement in forming a sakinah family in the perspective of Islamic family law, namely. First, to form a sakinah family, it is best if the prospective husband and wife make a marriage agreement which includes communication problems, personal and shared assets, biological needs (sex), economic problems, and appearance. Second, the marriage agreement includes a form of maslahah for married couples to achieve maqashid asy-syari'ah. Through a marriage agreement, what is the goal of the Shari'a, namely to achieve benefit can be realized or achieved.